Update on Mechanisms of Hormone Action Focus on Metabolism, Growth and Reproduction - Aimaretti with Paolo Marzullo, Gianluca; Prodam, Flavia (IntechOpen, 2011)
The purpose of the present volume is to focus on more recent aspects of the complex regulation of hormonal action, in particular in 3 different hot fields: metabolism, growth and reproduction. Modern approaches to the physiology and pathology of endocrine glands are based on cellular and molecular investigation of genes, peptide, hormones, protein cascade at different levels. In all of the chapters in the book all, or at least some, of these aspects are described in order to increase the endocrine knowledge.